identification of fungi and their toxins associated with imported rice grain to iraq (Baghdad Science Journal, 2005)
The study included the investigation of fungi ringed and inventory and Aflatoxins in rice and recorded average temperatures and humidity 22.75 degree Celsius and 13.2% respectively were obtained 1356 isolation innate possible diagnosis 15 species inherent in rice imported back to 8 races represented races b Fusarium , Cladosporium, Aspergillus and Alternaria